PERANCANGAN PERANGKAT LUNAK E – LEARNING PADA MATA PELAJARAN TIK (Teknologi Informasi dan Komunikasi) BERBASIS WEB STUDY KASUS DI SMP WALISONGO 2 SEMARANG (Information Technology and Telematics, 2013)
Learning methods performed by junior Walisongo 2 Semarang is still done by hand and sometimes less attracted students, causing saturation in understanding the lesson. Associated with the development of information technology is rapidly increasing, teaching and learning activities can be optimized by using information technology. The purpose of this study is to develop an e-learning application of ICT subjects at junior Walisongo 2 Semarang web-based. E-Learning system was created using PHP programming language and database (MySQL). E-Learning System is also designed using the tools of system design UML (Unified Modeling Language). It can be concluded that the E-learning system has been designed and implemented with facilities include user management, material management tick, and the input task will be much easier and give the material to the students. Keywords: E-learning, Learning PHP, MySQL, Website.